Evaluative names of personalities in sociocultural context (based on modern mass media) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article is devoted to the research of evaluative names of personalities in sociocultural context in modern mass media sources. It analyzes the classification of evaluative names of personalities in sociocultural aspect, it investigates evaluative connotation dynamism.
Keywords: evaluative names of personalities; sociocultural identification; social evaluation